Strategy for the creation of clinical grade hESC line banks that HLA-match a target population - Jacquet, Laureen (WILEY-VCH Verlag, 2013)
Here, we describe a pre-derivation embryo haplotyping strategy that we developed in order to maximize the efficiency and minimize the costs of establishing banks of clinical grade hESC lines in which human leukocyte antigen (HLA) haplotypes match a significant proportion of the population. Using whole genome amplification followed by medium resolution HLA typing using PCR amplification with sequence-specific primers (PCR-SSP), we have typed the parents, embryos and hESC lines from three families as well as our eight clinical grade hESC lines and shown that this technical approach is rapid, reliable and accurate. By employing this pre-derivation strategy where, based on HLA match, embryos are selected for a GMP route on day 3–4 of development, we would have drastically reduced our cGMP laboratory running costs.